2017
DOI: 10.15265/iy-2017-007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Data Reuse or Secondary Use: Current Status and Potential Future Progress

Abstract: SummaryObjective: To perform a review of recent research in clinical data reuse or secondary use, and envision future advances in this field. Methods: The review is based on a large literature search in MEDLINE (through PubMed), conference proceedings, and the ACM Digital Library, focusing only on research published between 2005 and early 2016. Each selected publication was reviewed by the authors, and a structured analysis and summarization of its content was developed. Results: The initial search produced 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 156 publications
1
105
0
4
Order By: Relevance
“…SRA and GEO are truly useful projects, enabling sharing and exchange of 'omic' data, which is important for data reuse [17]. An example demonstrates reuse of large amounts of data (over 5000 gene expression data-sets from GEO), where the different studies were integrated and revealed the overall structure of gene expression space across different tissues, which could not have been observed using any of the contributing studies individually [18].…”
Section: Discussionmentioning
confidence: 99%
“…SRA and GEO are truly useful projects, enabling sharing and exchange of 'omic' data, which is important for data reuse [17]. An example demonstrates reuse of large amounts of data (over 5000 gene expression data-sets from GEO), where the different studies were integrated and revealed the overall structure of gene expression space across different tissues, which could not have been observed using any of the contributing studies individually [18].…”
Section: Discussionmentioning
confidence: 99%
“…S.M. Meystre, C. Lovis, T. Bürkle, et al [15]; Y. Wang, L. Wang, M. Rastegar-Mojarad, et al [16] showed another fundamental feature of the EHR data extraction. This internal structural complexity determines the relationship between survey data and medical prescriptions (procedures, medications), taking into account the chronology of events, etc.…”
Section: Big Biomedical Data Mining: Related Workmentioning
confidence: 99%
“…High potential is expected from the reuse of such structured clinical data for secondary research purposes, for example when applied in epidemiological and health economic research, comparative effectiveness research, or health care quality improvement (2)(3)(4). The establishment of learning health care systems (LHCS) and the development of precision medicine are further examples of promising developments (5,6).…”
Section: Introductionmentioning
confidence: 99%